(untitled) (KYAMC Journal, 2022)
Background: Transversus Abdominis Plane (TAP) block is a regional anaesthetic technique used for postoperative pain management following abdominal surgery. Local anesthetics like bupivacaine can be used in this block and it can be performed in various approaches. Among them ultrasound-guided lateral and posterior approaches are popular. Objective: Aim of this study is to compare the effectiveness of lateral and posterior approaches of ultrasound-guided TAP block using bupivacaine in the management of post-operative pain after total abdominal hysterectomy under subarachnoid anesthesia. Materials and Methods: This randomized clinical trial was carried out in the Department of Anaesthesia, Analgesia and Intensive Care Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka. Total 90 patients were scheduled for elective total abdominal hysterectomy and assigned into two equal groups, group A and group B received ultrasound guided TAP block in lateral approach and in posterior approach respectively. Then patients were observed for pain intensity at rest and during deep breath by visual analog scale (VAS), after 1 hour, 2 hours, 4 hours, 6 hours, 12 hours and 24 hours of TAP block. The time of first analgesic demand was noted. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-22). Results: The mean pain intensity at rest and during deep breath was statistically significant (p<0.05) at 4, 6, 12 and 24 hours after TAP between two groups. The mean duration of first analgesic demand was 5.04±0.54 hours in group A and 6.59±0.69 hours in group B was statistically significant (p<0.05) between two groups. Conclusion: TAP block in posterior approach provided considerably effective postoperative analgesia in first 24 hours than lateral approach after total abdominal hysterectomy. KYAMC Journal Vol. 13, No. 02, July 2022: 66-71